Analysis of VSAT System Performance in Security and Communication Integrity of Indonesian Navy Headquarters - Sunu Harnoko; Franciskus Antonius Alijoyo (Jurnal Info Sains : Informatika dan Sains, 2023)
The development of satellite communications technology makes it easier for various groups and agencies to send and receive information and maintain confidentiality. In carrying out communications, the Indonesian Navy uses satellite technology in the form of VSAT. VSAT is an abbreviation for "Very Small Aperture Terminal", namely a signal receiving station from a satellite with a dish-shaped receiving antenna with a diameter of less than three meters. This research uses a qualitative approach that will analyze the performance of the VSAT system in maintaining the security and integrity of communications carried out by the Indonesian Navy. It is hoped that this research will provide an understanding of the use of modern satellite communications technology such as VSAT and its relevance for increasing security and maintaining the confidentiality of the Indonesian Navy